Pengelolaan BUMDes: Aspek Hukum dan Regulasi - Ninon Melatyugra; Indirani Wauran; Dyah Hapsari Prananingrum; Umbu Rauta; Yafet Y.W. Rissy (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2020)
The purpose of BUMDes formation is to improve the welfare of the village community. However, the community does not yet have a sufficient understanding of BUMDes. Based on this reason, CoRRDev UKSW carried out community service in accordance with lecturer duties in the field of Higher Education Tri Dharma. The community service aims to deeper public understanding of the legal and regulatory aspects concerning BUMDesa governance and management. The community service was done in the form of online counseling, which took attendance from participants from BUMDes members, village officials, and its community. The community service also covered an evaluation of BUMDes governance that was carried out by each participant. The participants gave a good impression of the community service that the event has added their knowledge about many legal aspects, which they needed to concern on BUMDes governance.